1976
DOI: 10.1212/wnl.26.8.703
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant striatonigral degeneration

Abstract: An autosomal dominant striatonigral degeneration is present in a family of Portuguese ancestry numbering in excess of 329 persons in eight generations. The illness begins in the second, third, or fourth decade, and progresses for about 15 years with parkinsonian rigidity, spasticity, spastic dysarthria, and abnormalities of eye movement. Neuropathologic findings are severe neuronal loss and astrocytic gliosis in the corpus striatum and substantia nigra, with a moderate neuronal loss in the dentate nucleus of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
91
0
5

Year Published

1984
1984
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(97 citation statements)
references
References 0 publications
1
91
0
5
Order By: Relevance
“…Its manifestations include cerebellar ataxia and progressive external ophthalmoplegia, associated in a variable degree with pyramidal signs, dystonia, rigidity, amyotrophies, and peripheral neuropathy. [1][2][3][4] The mutation associated with this disorder is the expansion of a (CAG) n tract in the coding region of the MJD1 gene, 5 which in normal individuals contains from 12 to 41 repeat units and in expanded chromosomes from 61 to 86 repeat units. [5][6][7] Although the mechanisms of trinucleotide repeat instability are still not understood, a variety of factors have been implicated as modulating intergenerational repeat instability in the diseases associated with dynamic mutations, namely the sex of transmitter, [6][7][8][9][10][11][12][13][14][15][16][17][18] the expanded repeat size in the transmitting parent, [8][9][10][11][12][18][19][20] the presence or absence of an interruption of the repeat, 16,[21][22][23][24][25] and even the sex of the descendent.…”
Section: Introductionmentioning
confidence: 99%
“…Its manifestations include cerebellar ataxia and progressive external ophthalmoplegia, associated in a variable degree with pyramidal signs, dystonia, rigidity, amyotrophies, and peripheral neuropathy. [1][2][3][4] The mutation associated with this disorder is the expansion of a (CAG) n tract in the coding region of the MJD1 gene, 5 which in normal individuals contains from 12 to 41 repeat units and in expanded chromosomes from 61 to 86 repeat units. [5][6][7] Although the mechanisms of trinucleotide repeat instability are still not understood, a variety of factors have been implicated as modulating intergenerational repeat instability in the diseases associated with dynamic mutations, namely the sex of transmitter, [6][7][8][9][10][11][12][13][14][15][16][17][18] the expanded repeat size in the transmitting parent, [8][9][10][11][12][18][19][20] the presence or absence of an interruption of the repeat, 16,[21][22][23][24][25] and even the sex of the descendent.…”
Section: Introductionmentioning
confidence: 99%
“…The striking clinical heterogeneity in SCA3 has been described since its initial description. In fact, in the 70's, the observation of three families of Azorean ancestry (Machado, Thomas and Joseph), living in the United States of America, by three distinct groups of researchers, led to the initial description of three apparently independent diseases 7,8,9 . The subsequent identification of several 1 Portuguese families living both in the Azores Islands and in Portugal mainland, including subjects presenting the three phenotypes described, led to the unification of the disease as a single genetic entity, with variable phenotypic expression 10 .…”
mentioning
confidence: 99%
“…The pathological hallmark of the disease is the presence of nuclear inclusions of aggregation-prone expanded ATXN3 in the patients' brains. Although ATXN3 is ubiquitously expressed (Paulson et al, 1997), only restricted neuronal populations of the central nervous system (CNS) are classically described as affected, namely the cerebellar dentate nucleus, pallidum, substantia nigra, thalamus, subthalamic, red, and pontine nuclei, cranial nerve nuclei and the anterior horn and Clarke's column of the spinal cord (Romanul et al, 1977;Rosenberg et al, 1976;Woods and Schaumburg, 1972). Recent pathological studies have suggested that the extension of CNS degeneration in MJD patients at end stages may be more widespread, including the visual, auditory, vestibular, somatosensory, ingestion-related, dopaminergic and cholinergic systems (Rub et al, 2008).…”
mentioning
confidence: 99%